HISTOPATHOLOGICAL CHANGES OF MALE MICE KIDNEYS TREATED WITH FRESH ALOE VERA WHOLE LEAF EXTRACT (Iraqi Journal of Medical Sciences, 2016)
Background:Aloe vera is an evergreen perennial plant widely used in modern herbal practice and is often available in proprietary herbal preparations. Evidence of efficacy is strongest for the laxative effects of Aloe vera latex; however the anthraquinones in the latex are associated with considerable risks.Objective:To investigate the histopathological changes of kidney tissues of male mice administered low dose of whole leaf fresh Aloe vera extract.Methods:Forty immature male Swiss Webster mice divided into two equal groups (experimental and control) (G and C respectively). The experimental group (G) was given 20 µl of Aloe vera extract orally for 21 days. While the control groups (C) were given by the same dose and route of administration with normal saline only. After six weeks (around puberty), the male were sacrificed to get their kidneys, then fixed with 10% formalin, and histological sections with a thickness of 5 microns were prepared.Results: Histological studies of mice kidneys from groups that consume low dose fresh Aloe vera whole leaf extracts showed disrupted entire structure of kidneys including degenerative changes in most parenchymatous elements in comparison with control.Conclusions:Using low doses of fresh Aloe vera whole leaf extract induce adverse effects on the histological features of mice kidneys and impaired their entire structure.Key words:Aloe vera, Kidney, anthraquinones, whole leaf extract.
Keywords: Aloe vera; Kidney; anthraquinones; whole leaf extract